2017
DOI: 10.1161/strokeaha.116.016020
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Motor Recovery After Stroke

Abstract: URL: http://www.anzctr.org.au. Unique identifier: ANZCTR12611000755932.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 14 publications
8
128
1
2
Order By: Relevance
“…The proportional recovery rule is attractive party because it formalises the popular, clinical intuition that initial symptom severity is by far the most, and perhaps the only, important predictor of recovery after stroke. The rule is also striking because it implies that recovery is simple and consistent across patients (non-fitters notwithstanding), and because that implication appears to be justified by an increasing number of extremely strong empirical results 3,7,[9][10][11][12][13][14]21,28,30 . That incredible, empirical power has even begun to encourage the search for some deeper, general recovery mechanism which cuts across cognitive domains 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportional recovery rule is attractive party because it formalises the popular, clinical intuition that initial symptom severity is by far the most, and perhaps the only, important predictor of recovery after stroke. The rule is also striking because it implies that recovery is simple and consistent across patients (non-fitters notwithstanding), and because that implication appears to be justified by an increasing number of extremely strong empirical results 3,7,[9][10][11][12][13][14]21,28,30 . That incredible, empirical power has even begun to encourage the search for some deeper, general recovery mechanism which cuts across cognitive domains 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in support of this 'proportional recovery rule' is rapidly accumulating, as summarised by Stinear in a recent review 2 . In five separate studies since 2015 [3][4][5][6][7] , researchers used the Fugl-Meyer test to assess stroke patients' upper limb motor function within two weeks after stroke onset, and then again either three or six months post-stroke. The results were consistent with earlier observations 8,9 that most patients recovered around 70% of lost upper limb function.…”
Section: Introductionmentioning
confidence: 99%
“…35 Based on the congruency of these findings with the human literature, it is plausible that common biological stroke recovery processes that are engaged by these variables might exist across mammalian species. 36 In humans, it has been demonstrated that this proportional recovery rule can be used to predict recovery of impairments within a variety of functional domains, including both upper 32,33,37 and lower limbs, 38 aphasia, 39 and visual neglect. 40 To address this secondary objective, we assessed whether our model of initial poststroke impairment, cortical infarct volume, and rehabilitation intensity 35 could be generalized as predictors of recovery on an additional forelimb motor task (single-pellet reaching).…”
mentioning
confidence: 99%
“…That is, the observed recovery of a given individual can be predicted based on that individual's initial impairment: approximately 70% of their maximal potential for recovery . This is known as the proportional recovery rule, and has been shown valid for the recovery of movements (including balance control), aspects of cognition, visuospatial neglect, and aphasia . There is variability in this recovery profile whereby the expression of proportional recovery in the motor domain depends on the integrity of the corticospinal tract .…”
Section: Current Challenges In the Field Of Stroke Recoverymentioning
confidence: 99%
“…45 This is known as the proportional recovery rule, 14 and has been shown valid for the recovery of movements (including balance control), aspects of cognition, visuospatial neglect, and aphasia. [45][46][47][48][49][50][51][52] There is variability in this recovery profile whereby the expression of proportional recovery in the motor domain depends on the integrity of the corticospinal tract. 51,52 For example, stroke survivors for whom a motor evoked potential (MEP) can be elicited demonstrate proportional recovery, in contrast to those who do not have an MEP.…”
Section: Current Challenges In the Field Of Stroke Recoverymentioning
confidence: 99%